Cross-Disciplinary Science Teaching in Bilingual Montessori Classrooms: Evidence from a Pre-service English teacher’s internship program - Agnestin Mayeli Elu Loy; Bernardus K. Danibao (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
Cross-disciplinary teaching has emerged as a significant component in a bilingual school program in Indonesia. However, empirical evidence regarding how cross-disciplinary teaching effectively supports bilingual Science learning remains scarce. This study examines the implementation of cross-disciplinary Science teaching by an English Education student during a teaching internship program in a bilingual Montessori classroom by integrating Content and Language Integrated Learning, Montessori-inspired learning, and Role Play. Using a qualitative case study design, data were collected through classroom observations, field notes, lesson documentation, and reflective teaching records, then analyzed using thematic analysis. The findings reveal that integrating these approaches fostered student engagement by promoting active participation, collaborative inquiry, and meaningful bilingual communication during Science learning. Furthermore, the study demonstrates that cross-disciplinary teaching can function as pedagogical innovation when supported by integrated instructional strategies combining language scaffolding, experiential learning, and student-centered approaches. This study proposes an integrated instructional framework for bilingual Science education and provides recommendations for teacher education institutions and partner schools to equip preservice teachers with the skills to integrate cross-disciplinary teaching lessons prior to their internship programs.